2019
DOI: 10.15405/epsbs.2019.07.97
|View full text |Cite
|
Sign up to set email alerts
|

Parent Image As An Integral Indicator Of Parenthood Subculture

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…A woman's lifestyle changes dramatically after giving birth. A well-educated, socially active woman is suddenly torn from her usual lifestyle and social circle, her world is narrowed to an apartment and a playground [18]. Many studies have shown that the women' postpartum period is accompanied by: varying degrees of depression; social misadaptation; violation of the system of relationships in the family, and even divorce; increased responsibility; increased excitability, irritability; an increase in nervous tension, mood swings and, as a result, emotional burnout, screams and mental breakdowns on the child.…”
Section: The Main Partmentioning
confidence: 99%
“…A woman's lifestyle changes dramatically after giving birth. A well-educated, socially active woman is suddenly torn from her usual lifestyle and social circle, her world is narrowed to an apartment and a playground [18]. Many studies have shown that the women' postpartum period is accompanied by: varying degrees of depression; social misadaptation; violation of the system of relationships in the family, and even divorce; increased responsibility; increased excitability, irritability; an increase in nervous tension, mood swings and, as a result, emotional burnout, screams and mental breakdowns on the child.…”
Section: The Main Partmentioning
confidence: 99%